2014
DOI: 10.1136/bmjopen-2014-006327
|View full text |Cite
|
Sign up to set email alerts
|

Survival of patients with alcohol use disorders discharged from an emergency department: a population-based cohort study

Abstract: ObjectivesThe aim was to study the cause-specific mortality of users of the emergency department (ED) who received a diagnosis of alcohol use disorder (AUD) in comparison with mortality of other users of the department.DesignA population-based prospective cohort study.ParticipantsAll patients aged 18 years and above who were subsequently discharged home from the ED during the years 2002–2008. A total of 107 237 patients were followed by record linkage to a nationwide cause-of-death registry: 1210 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Given that the included studies were predominantly conducted in advanced economies, recruited mostly middle-aged males, and that we reported rates for combined genders, the findings of this review are likely to be generalizable to similar AUD populations and not to other AUD populations with different demographic, clinical, socioeconomic, or other characteristics. An example of such a population might be that described by Gunnarsdottir et al, 58 where the AUD population was sampled in the emergency care setting, and consisted of a lesser proportion of males (63.7%) than ours and had mortality rates less than those found in this review (e.g., allcause mortality 12.62/1000 py vs. 28.08/1000 py). Secondly, we found significant heterogeneity in the metaanalyzed estimates of pooled crude mortality rates.…”
Section: Strengths and Limitationsmentioning
confidence: 72%
“…Given that the included studies were predominantly conducted in advanced economies, recruited mostly middle-aged males, and that we reported rates for combined genders, the findings of this review are likely to be generalizable to similar AUD populations and not to other AUD populations with different demographic, clinical, socioeconomic, or other characteristics. An example of such a population might be that described by Gunnarsdottir et al, 58 where the AUD population was sampled in the emergency care setting, and consisted of a lesser proportion of males (63.7%) than ours and had mortality rates less than those found in this review (e.g., allcause mortality 12.62/1000 py vs. 28.08/1000 py). Secondly, we found significant heterogeneity in the metaanalyzed estimates of pooled crude mortality rates.…”
Section: Strengths and Limitationsmentioning
confidence: 72%
“…A second study of AUD in Iceland identified 1200 patients with AUD among over 100,000 emergency department attendances with seven years’ follow-up [ 31 ]. AUD was associated with a higher risk of suicide, but with only 15 deaths from suicide the estimates were imprecise.…”
Section: Discussionmentioning
confidence: 99%
“…Of the initial 5904 records screened for inclusion, a total of 10 studies were included in the systematic review, seven of which were eligible for quantitative synthesis [27,[32][33][34][35][36][37], in addition to two secondary US data sources (i.e. NESARC and NHIS) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%